Call to Action: Urgent Challenges in Cardiovascular Disease. Issue 9 (26th February 2019) - McClellan, Mark; Brown, Nancy; Califf, Robert M.; Warner, John J.
Abstract : Although advances in care have spurred improvements in cardiovascular outcomes, cardiovascular disease remains the leading cause of death in the United States and around the world. Previous declines in cardiovascular disease mortality have slowed and even reversed for certain demographics. Further concerns exist with regard to cardiovascular drug innovation, quality of care, and healthcare costs. The Value in Healthcare Initiative–Transforming Cardiovascular Care, a collaboration of the American Heart Association and Duke University, Robert J. Margolis, MD, Center for Health Policy, aims to increase access to and affordability of cardiovascular treatment and to decrease barriers to care. The following Call to Action describes trends in cardiovascular care, identifies gaps in areas of cardiovascular disease prevention and treatment, highlights challenges with medical product innovation, and finally, outlines a series of learning collaboratives that will aid in the development of road maps for transforming cardiovascular care.